SELF-CONTROL IN THE FINANCIAL MANAGEMENT OF STUDENTS: A STUDY OF LITERACY, FINTECH, AND INCOME - Sri Puji Lestari; Ryan Prastika (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of Financial Literacy, Financial Technology, and Income on Financial Management among Evening Class Students of the Management Study Program, Faculty of Economics and Business, UMSU, Batch 2021, with Self-Control as a moderating variable. This research employs a quantitative approach using a survey method. Data were collected through questionnaires from 294 respondents, determined using the Slovin formula. The data were analyzed using Structural Equation Modeling (SEM) with the Smart-PLS software to assess both direct and moderating effects among variables. The results indicate that Financial Literacy has a significant effect on Financial Management. However, Financial Technology and Income do not have a significant effect. Furthermore, Self-Control moderates the relationship between Financial Literacy and Financial Management, but does not moderate the influence of Financial Technology and Income on Financial Management. This study introduces novelty by incorporating Self-Control as a moderating variable in the relationship between Financial Literacy, Financial Technology, and Income with Financial Management among evening class students—a group rarely explored in previous studies. The findings underscore the importance of enhancing financial literacy and self-control to improve students' financial management, particularly for those balancing work and study responsibilities.